Local digital journalism . History and current uses. A study of VilaWeb local and Madridiario - Domínguez, David Caldevilla; Visa Barbosa, Mariona (Anàlisi, 2014)
This paper presents an overview of the Spanish local digital media with the aim to see how the local media have adapted to new journalism’s characteristics. First, it offers a historical review of online journalism, it shows a list of the advantages and disadvantages that new media are offering and a description of the current situation of digital media market. The second part analyzes two cases of local digital media: Vilaweb in Catalonia (specifically the case of Vilaweb Mollerussa) and Madridiario, in the region of Madrid. It aims to evaluate their use of digital resources, such as the level of interaction with the reader-user and the personalized access to the information. This analysis shows how the potential of journalism 2.0 is not yet established in the digital local media. While the national media taks full advantage of the possibilities of digital media, like blogs or forums of opinion, the local media have not yet achieved a solid ground for popular segmentation to encourage the participation of citizens.